Diffuse Epithelial Downgrowth Associated With an Extruded Anterior Chamber Intraocular Lens Haptic. Issue 6 (November 2015) - Lin, Phoebe; Jeng, Bennie H.
Abstract : Background: Anterior chamber intraocular lenses (ACIOL) have been known to be associated with several complications, including endophthalmitis. We present a patient who developed another type of severe complication: epithelial downgrowth associated with an extruded footplate of an ACIOL. Methods: Case report. Results: A 70-year-old schizophrenic woman underwent implantation of an ACIOL during cataract extraction that was complicated by posterior capsular rupture, erratic patient movement, conversion to extracapsular cataract extraction (ECCE), and vitreous loss in her left eye. She subsequently presented with progressively decreasing vision, and she was found to have extensive epithelial downgrowth that also resulted in neovascularization of the iris and recurrent hyphemas. The patient elected to have the ACIOL explanted, and at the time of the surgery, it was noted that one of the footplates of the ACIOL was protruding through the original ECCE wound. We believe that the extrusion of this footplate was one contributing factor toward severe epithelial downgrowth. Conclusions: Although exposure of an ACIOL haptic is a very rare occurrence, it can have severe consequences, including epithelial downgrowth.